Myosin II-mediated focal adhesion maturation is tension insensitive. - Jonathan Stricker; Yvonne Beckham; Michael W Davidson; Margaret L Gardel (PLoS ONE)
Myosin II motors drive changes in focal adhesion morphology and composition in a "maturation process" that is crucial for regulating adhesion dynamics and signaling guiding cell adhesion, migration and fate. The underlying mechanisms of maturation, however, have been obscured by the intermingled effects of myosin II on lamellar actin architecture, dynamics and force transmission. Here, we show that focal adhesion growth rate stays constant even when cellular tension is reduced by 75%. Focal adhesion growth halts only when myosin stresses are sufficiently low to impair actin retrograde flow. Focal adhesion lifetime is reduced at low levels of cellular tension, but adhesion stability can be rescued at low levels of force by over-expression of α-actinin or constitutively active Dia1. Our work identifies a minimal myosin activity threshold that is necessary to drive lamellar actin retrograde flow is sufficient to permit focal adhesion elongation. Above this nominal threshold, myosin-mediated actin organization and dynamics regulate focal adhesion growth and stability in a force-insensitive fashion.